Transport behavior of particulate organic matter in river water during snow melting in the Ishikari, Tokachi, Teshio and Kushiro Rivers, Japan (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Both ?14C and ?13C were used to study the transport behavior of particulate organic matter (POM) in the Ishikari, Tokachi, Teshio and Kushiro rivers in Japan. Water samples were collected once a month in April and May in 2004 and 2005 during snow melting. Positive correlations were found between ?14C and particulate organic carbon (POC) content. Negative correlations were found between ?14C and increased water level. These results indicate that the river systems showed similar transportation behavior during snow melting because of the variation of water level and water discharge. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15597 J. Asiat. Soc. Bangladesh, Sci. 38(2): 163-173, December 2012